Development and Quality Evaluation of Quick-Frozen Fruit-and-Berry Desserts - Batuch M. Guseynova; Islam H. Asabutaev; Tatyana I. Daudova (Техника и технология пищевых производств)
New functional foods based on local vegetal raw materials can accelerate the implementation of the Strategy for Improving Food Quality in the Russian Federation through 2030. The present research aimed at developing formulations and technology for new functional quick-frozen fruit-and-berry desserts. The study featured four dessert mixes: apricot-persimmon-buckthorn, apricot-feijoa-sloeberry, apricot-persimmon-cornel, and apricot-feijoa-currant. The quality of the finished products was evaluated using conventional methods according to the mass concentration of sugars, solids, pectin, titrated acids, vitamin C, β-carotene, and minerals. The desserts were tested for toxic elements based on the atomic absorption method. The microbiological safety parameters were determined after six months of refrigeration storage (t = –18°C) using standard methods. The physicochemical data made it possible to design formulations where all components complemented each other’s beneficial properties. To stabilize the quality and obtain the optimal structural and mechanical properties, the formulations were completed with a sugar-pectin solution (380 g per 1 kg) with 30% sugar and 1.3% pectin. The mass concentration of some biologically active substances made the desserts functional: 250 g of each product satisfied the daily intake of pectin substances by 51.9–61.3%, vitamin C – by 42.9–123.4%, β-carotene – by 22.5–47.5%, iron – by 8.9–20.5%, and iodine – by 13.3–30.0%. The new quick-frozen functional fruit-and-berry desserts proved to have advanced organoleptic indices and met the safety requirements provided by Technical Regulations of Customs Union TR TC 021/2011.